Symbol in the Context of Psychoanalytic and Sense Interpretation - Irina V. Abakumova; Elena А. Koltunova; Pavel N. Ermakov (Rossijskij psihologičeskij žurnal., 2016)
The paper considers the modern interpretation of the symbol as a psychological category in the context of the theory of sense and sense-creation. The study ofthe symbol has a long history of various scientific interpretations. Modern psychology makes some substantial additions to the understanding of the mechanisms ofthe formation of symbols at the level of public conscience, aswell as at the level ofpersonal consciousness. The main purpose of the paper is to characterize the specificity of the interpretation of the symbol as a certain sense value. Theauthors revealed and described the genetic relationship ofthe interpretation ofsymbolization in two different psychological schools: psychoanalysis and the theory of sense-creation. The authors suggested differentiating symbols in accordance with the characteristics of their representation in the system of personal values. Thus, the authors introduce the “concept-symbol” category. Concepts-symbols are not similar to traditional concepts owing to their universal functional filling. Concepts-symbols are a sort oftransformers; they bear meanings that not only direct the person’s understanding ofa context but also disclose the sense and its possible variability. The symbol includes two forms of senses: extrapersonal and interpersonal. Hence, the symbol is able toinspire the procedure of sense-creation in the subject who cognizes its meanings. The “decrystallization” ofpersonal comprehension, where the very concept is its bearer, underlies theinteriorization of concepts-symbols. The formation and improvement of the person’s sense sphere is possible through the use of the conceptual-symbolic system, which considers concepts-symbols of various meanings (symbols: signs, properties, composition, and metaphors).